Consortial Usage of Electronic Journals in Turkey - Karasözen, Bülent (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
In this short article the increase in the usage of electronically licensed databases by ANKOS (Anatolian University Libraries Consortium) is explained with reference to COUNTER compliant e-journal collections. The diversity of usage among the universities and the cost-effectiveness of electronically available databases with the consortium is explained, taking into account the special characteristics of Turkish university libraries, the rapid increase of students and newly established universities, as well as the growth of scientific publications.